Case Study: Bronkopneumonia disertai Perimiokarditis pada Anak Usia 16 Bulan - Diyah Arum Setiasih; Lita Farlina; Kiki Rizki Maharani (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Bronchopneumonia remains a major cause of morbidity and mortality in children, particularly in early life, and may be accompanied by cardiac complications such as perimyocarditis. This report describes the clinical presentation, diagnostic findings, management, and outcome of a 16 month old female child admitted with progressive shortness of breath, high fever, productive cough, and rhinorrhea. The patient presented with initial symptoms of lower respiratory tract infection with respiratory distress and suspected cardiac involvement as indicated by a heart murmur and gallop on auscultation. Chest radiography showed bilateral bronchopneumonia with cardiomegaly. During hospitalization, the patient developed rapid clinical deterioration with decreased consciousness, respiratory failure, and shock, requiring transfer to the Pediatric Intensive Care Unit. Further evaluation by echocardiography demonstrated left ventricular dilatation, global hypokinetic left ventricle, ejection fraction of 30%, moderate mitral regurgitation, and minimal pericardial effusion. Based on the clinical and supporting  findings, the final diagnosis was perimyocarditis with bronchopneumonia. The patient's condition showed significant clinical improvement after being given oxygenation therapy, antibiotics and heart failure therapy. This case highlights the importance of early recognition of cardiac involvement in children with bronchopneumonia, especially in those with rapid deterioration and hemodynamic instability.